Penyuluhan Manajemen Nyeri Persalinan Menggunakan Effleurage Massage Pada Ibu Hamil Trimester III - Rini Rahmayanti; Riski Oktafia (Jurnal Abdimas Madani dan Lestari (JAMALI), 2022)
The basic needs of the maternity mother include the nutritional needs of the delivery mother, the need for elimination, the need for positioning, psychological needs, and the need for pain reduction. Efforts to reduce pain are important and need to be considered by health workers / birth attendants through efforts to overcome labor pain. Labor pain can cause suffering for the mother and her health.This can have a negative effect on the mother-infant relationship. The purpose of this activity is to provide knowledge to pregnant women about the management of labor pain using effleurage massage. This activity is carried out using lecture, discussion and demonstration methods. This activity was held on October 10, 2020 and was attended by 20 pregnant women. The results obtained were an increase in the knowledge, understanding, and ability of participants in understanding the material presented in this service activity. It was found that 80% of the audience who attended were able to mention the meaning of labor pain, 75% of the audience who attended were able to mention and demonstrate the method of effleurage massage. This health education can be carried out by health workers to increase the knowledge of pregnant women about the management of labor pain using effleurage massage.